A Model for Calculation of a Productivity Bonus - Sánchez de León, José Alfredo (Universidad Autónoma de Queretaro, 2017)
A productivity bonus represents a defrayal that some working places extents to their workers, in order to gratificate them due to the accomplishment of some productive goals or objectives. It depends upon any organization the establishment of some method to calculate this payment and to define on which variables the calculation would be based upon. The objective of this document concerns the raising of a mathematical model that could be deployed towards the computation of this quantity. A mathematical analysis is carried out on top of the basic structure of a given fixed set of an enterprise process performance metrics, or key performance indicators (KPIs). The model takes as inputs the goals and control limits (parameter values of the metrics that are commonly found on many organizations) (Duke, 2013), their value accomplishment result, and a free parameter. A typical real life example is exposed, as a case of study, where it is applied this calculation scheme; as the result, a productivity bonus was successfully calculated, so concluding that this result can be a useful device to carry out this task.